2009
DOI: 10.1124/jpet.109.156471
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine Antagonizes the Effects of Increased Late Sodium Current on Intracellular Calcium Cycling in Rat Isolated Intact Heart

Abstract: Pathological conditions, including ischemia and heart failure, are associated with altered sodium channel function and increased late sodium current (I Na,L ), leading to prolonged action potential duration, increased intracellular sodium and calcium concentrations, and arrhythmias. We used anemone toxin (ATX)-II to study the effects of increasing I Na,L on intracellular calcium cycling in rat isolated hearts. Cardiac contraction was abolished using paralytic agents. Ranolazine (RAN) was used to inhibit late I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
(46 reference statements)
3
26
0
Order By: Relevance
“…Spatial correlation or coarser patterns of TT disruption may cause more complex spatiotemporal behaviors of Ca alternans and other Ca cycling dynamics which need to be addressed in future studies. Refractoriness of Ca release is controversial, with time constants measured experimentally ranging from 100 to 650 ms [5357]. Some studies have concluded that the refractoriness is mainly related to SR refilling and luminal Ca sensing, while others show that it is due to recovery of the RyR channels.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial correlation or coarser patterns of TT disruption may cause more complex spatiotemporal behaviors of Ca alternans and other Ca cycling dynamics which need to be addressed in future studies. Refractoriness of Ca release is controversial, with time constants measured experimentally ranging from 100 to 650 ms [5357]. Some studies have concluded that the refractoriness is mainly related to SR refilling and luminal Ca sensing, while others show that it is due to recovery of the RyR channels.…”
Section: Discussionmentioning
confidence: 99%
“…This drug is known to reduce Na ϩ channel leak through Nav1.4, as well as other Na ϩ channels (57,58). Ranolazine also antagonizes reversemode Na ϩ -Ca 2ϩ exchange in cardiomyocytes through both direct (59) and indirect (60,61) means. Finally, ranolazine is known to result in lower resting intracellular Na ϩ levels in cardiomyocytes (62,63).…”
Section: Resultsmentioning
confidence: 99%
“…The RyR model developed by Restrepo et al (14) incorporated calsequestrin-mediated SR luminal Ca regulation, whereas recent experiments have demonstrated a luminal Ca-sensing site in the RyR mediating this effect (63). Moreover, the refractoriness of Ca release is controversial, with a wide range of experimentally measured values (64)(65)(66)(67)(68)(69) and different proposed causes. Different refractory period choices may impact the Ca cycling dynamics, as well as the voltage dynamics caused by Ca-voltage coupling.…”
Section: Limitationsmentioning
confidence: 99%